On the Road to Inclusion: A Multifaceted Examination of Transportation Challenges Faced by Individuals with Disabilities - Alcura, Guezin Akyildiz (MDPI, 2025)
The Sustainable Development Goals (SDGs) set forth by the United Nations aim to eradicate poverty, protect the environment, and promote global prosperity by 2030. Within this framework, Goal 11 targets explicitly sustainable cities and communities, emphasizing the need for accessible, safe, and sustainable transportation systems for all individuals, including those with disabilities. However, despite these aspirations, individuals with disabilities often face unique challenges and barriers in accessing transportation services. This study delves into the complexities of transportation accessibility for people with disabilities, aiming to understand their perceptions and expectations of service quality regarding reliability, tangibles, cleanliness, safety, comfort, personnel, and stops. In a comprehensive survey involving 302 individuals with disabilities, data were collected considering strata such as visual impairment, hearing impairment, chronic illness, and physical disability. In the study where cluster analysis was applied to examine the common and unique assessments of individuals with disabilities, both demographic characteristics and transportation habits were evaluated to determine the most effective inputs. The optimal results were obtained using disability level, car ownership, access to stops, and frequency of service use, while the inclusion of other sociodemographic variables (such as age and income) negatively affected the quality of the clustering process. By analyzing service quality independently for each cluster, the study unveils potential variations in how people with disabilities perceive and evaluate transportation services. The findings shed light on the distinct evaluation approaches employed by people with disabilities based on their characteristics, highlighting the need for tailored transportation planning and policy-making solutions. For example, in the overall assessment of individuals with disabilities, vehicle ergonomics was not highlighted as an area for improvement, but it emerged as the aspect with the least satisfaction among individuals with higher levels of disability. By addressing these nuances, policymakers and stakeholders can better understand and meet the diverse needs of people with disabilities, contributing to the creation of more inclusive and accessible transportation systems in line with the SDGs.
Keywords: passengers with disabilities; public transportation; cluster analysis; service quality; inclusivity; PUBLIC TRANSPORT; ACCESSIBILITY; PEOPLE; ACCESS; OPPORTUNITIES; NEEDS; Science & Technology - Other Topics; Environmental Sciences & Ecology